Barter in the Modern Era: Study of Buying and Selling Rice Fields with Rice Fields from Sharia Economic Law Perspective in Tanjung Pauh Mudik Village - Busni, Darti; Sumanti, Eva; Witro, Doli; Alghani, Raid (Fakultas Syariah IAIN madura, 2024)
This article aims to determine the practice of buying and selling paddy fields with paddy fields carried out in Tanjung Pauh Mudik Village, Danau Barat District, Kerinci Regency. The practice of buying and selling rice fields focuses on how prices are determined when buying and selling and how sharia economic law reviews the buying and selling practices. This research is qualitative field research which aims to understand the phenomenon of what the researcher observes. The approach used in this research is a sociological approach. The primary data comes from data related to the buying and selling of rice fields that occurred in Tanjung Pauh Village. Meanwhile, secondary data is supporting data, namely in the form of archives, documentation, and books related to the issue of buying and selling rice fields with rice fields. The data collection techniques used were observation, interviews, and documentation. The data analysis technique used is the Miles and Huberman data analysis technique which consists of data collection, data reduction, data display (data presentation), and conclusion drawing/verification (drawing conclusions). The results of the analysis concluded that the practice of buying and selling rice fields for rice fields carried out by the people of Tanjung Pauh Mudik Village has been carried out for a long time and no one knows since when they have been doing this. The factors that encourage people to sell rice fields in Tanjung Pauh Mudik Village include first, so that the rice fields, which are their main land for earning a living, are not lost or reduced. Second, to add or expand the rice fields they own. Third, improve the welfare of the population. The sale and purchase of rice fields and rice fields in Tanjung Pauh Mudik Village according to the perspective of sharia economic law is included in the barter buying and selling system. Buying and selling in this system is permitted as long as it meets the specified conditions and pillars. Most of the buying and selling of paddy fields and rice fields carried out in terms of sharia economic law has fulfilled the requirements and terms of barter buying and selling, although there are still some things that have not been fulfilled, including firstly in terms of the requirements for mitlan bi mitslin and in terms of the person who is entering into the contract (subject).